Evaluation of Lymphoproliferative Disease and Increased Risk of Lymphoma in Activated Phosphoinositide 3 Kinase Delta Syndrome: A Case Report With Discussion - Pham, Michele N.; Cunningham-Rundles, Charlotte (Frontiers in Pediatrics, 2018)
Activated phosphoionositide-3 kinase delta syndrome (APDS) is a rare disorder caused by activating mutations in phosphoionositide 3-kinase delta (PI3Kδ). This syndrome usually presents in childhood with recurrent sinopulmonary infections and immune deficiency as is seen in the case discussed in this report. Patients with APDS also experience other complications including lymphoid hyperplasia, autoimmunity, increased susceptibility to herpes viruses, especially Epstein-Barr virus and cytomegalovirus, and an increased incidence of B-cell lymphoma. The clinical implications for lymphoid hyperplasia and lymphoma are profound and frequently, it is challenging to distinguish between the two. This case report is of a young girl with a mutation in PIK3CD, the gene encoding the catalytic subunit of PI3Kδ, who presents with asymmetrical cervical lymphadenopathy and parotid swelling. After little improvement in lymphadenopathy on antibiotics, an excisional biopsy of a cervical lymph node was obtained which was initially concerning for lymphoma. This case recounts the clinical decisions made to evaluate this lymphadenopathy and concern for malignancy due to the increased incidence of B-cell lymphoma in this population. It was concluded after careful evaluation of her lymph node histology and cytometry, bone marrow biopsy, and CSF studies that her findings were consistent with lymphoid hyperplasia and not lymphoma and she was treated with rituximab. This case highlights the many comorbidities present in patients with this disease and the current treatments for complications in patients with APDS, including new targeted therapies.